Effectiveness of construction industry payment and Adjudication Act (CIPAA) in remedying payment issues among sub-contractors - Tay, Zi Keng; Kong, Sio Kah (INTI International University, 2018)
Payment issues are prevalently rooted in the Malaysian construction industry, whereby upstream players have abused their payment obligation to force the downstream players such as Sub-Contractors to accept the onerous conditions. Meanwhile, there is no sanction for the default available in several Sub-Contract Agreements to facilitate the cash flow and yet, seeking dispute resolution from arbitration and litigation is expensive and time consuming. As a result, the unpaid Sub-Contractors with weak financial capacity are often forced to encounter severe cash flow problems and eventually led to adverse impact to construction industry. CIPAA was enacted in 2012 to facilitate regular and timely payment. However, the effect of adjudication decision is temporary binding, which might lead to a meaningless decision if it is resisted by losing party. Therefore, this research objectives are to identify the pertinent features of CIPAA in remedying payment issues and investigate the effectiveness of provisions set out under CIPAA in remedying payment issues. This study is targeted to the CIDB Grade 7 Sub-Contractors located in Selangor and Johor and quantitative questionnaires survey method is adopted. The results shows that CIPAA is an effective dispute resolution to overcome conditional payment provisions and it is able to minimize cash flow problems due to its speedier, contemporaneous and extensive remedies to recover payment. However, cost of adjudication fee and temporary binding decision under CIPAA are the major concern for Sub-Contractors to apply CIPAA as a dispute resolution.